2021
DOI: 10.1007/s00285-021-01601-6
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to “Best match graphs”

Abstract: Two errors in the article Best Match Graphs (Geiß et al. in JMB 78: 2015–2057, 2019) are corrected. One concerns the tacit assumption that digraphs are sink-free, which has to be added as an additional precondition in Lemma 9, Lemma 11, Theorem 4. Correspondingly, Algorithm 2 requires that its input is sink-free. The second correction concerns an additional necessary condition in Theorem 9 required to characterize best match graphs. The amended results simplify the construction of least resolved trees for n-cB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…In [3,4,5], BMGs have been characterized in terms of certain sets of rooted triples that easily can be constructed for every given vertex-colored digraph: For vertex-colored digraphs that are associated with binary trees, we will furthermore need…”
Section: Best Match Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [3,4,5], BMGs have been characterized in terms of certain sets of rooted triples that easily can be constructed for every given vertex-colored digraph: For vertex-colored digraphs that are associated with binary trees, we will furthermore need…”
Section: Best Match Graphsmentioning
confidence: 99%
“…Best match graphs then collect the best match information for a family of related genes from different species. Because of their close connection to the practically important problem of orthology detection, which often starts from reciprocal best matches, BMGs have been studied in some detail [1,2,3,4,5]. Two-colored BMGs, furthermore, are characterized by four properties of the out-neighborhoods of its vertices.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, we have shown that such trees can be inferred e.g. as the least resolved trees from best match data [ 9 , 10 ] and from information of horizontal gene transfer [ 11 , 12 ]. Denoting with the set of “clusters” in T , we recently showed that the latter type of data can be explained by a common evolutionary scenario if and only if (1) both the best match and the horizontal transfer data can be explained by least resolved trees and , respectively, and (2) the union is again a hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…Defs. 1 and 2 below), form a very restrictive class of colored digraphs [6,7]. Empirically determined best hit data therefore will in general not satisfy the defining properties of BMGs.…”
Section: Introductionmentioning
confidence: 99%
“…A formal definition of triple consistency will be provided in the next section. In [7], it was shown that a vertex-colored digraph ( � G = (V , E), σ ) is a BMG if and only if (a) the set of informative triples R( G, σ ) is consistent and (b) the BMG � G(T , σ ) of the corresponding so-called Aho tree T := Aho (R( � G, σ ), V ) coincides with ( G, σ ) . In general, the Aho tree Aho (R, V ) of a consistent set of triples R on a set V is a least resolved supertree of all the triples in R .…”
Section: Introductionmentioning
confidence: 99%